Estimation of Outage Capacity for Free Space Optical Links Over I-K and K Turbulent Channels - Nistazakis, Hector E.; Tsigopoulos, Andreas D.; Hanias, Michalis P.; Psychogios, Christos. D.; Marinos, Dimitris; Aidinis, Costas; Tombras, George S. (Společnost pro radioelektronické inženýrství, 2011)
The free space optical communication systems are attracting great research and commercial interest due to their capability of transferring data, over short distances, with high rate and security, low cost demands and without licensing fees. However, their performance depends strongly on the atmospheric conditions in the link’s area. In this work, we investigate the influence of the turbulence on the outage capacity of such a system for weak to strong turbulence channels modeled by the I-K and the K-distribution and we derive closed-form expressions for its estimation. Finally, using these expressions we present numerical results for various link cases with different turbulence conditions.
Keywords: Atmospheric turbulence; outage capacity; I-K distribution; K-distribution; free space optical channels